Enantioselective HS-SPME-GC-MS for Authentication of Natural and Synthetic Strawberry Flavour in Syrups - Karolína Průchová; Adéla Grégrová; Hana Helísková; Vojtěch Kružík; Helena Čížková (Polish Journal of Food and Nutrition Sciences)
Demand for a reliable distinction of the strawberry flavour naturalness stood in the beginning of this research. An efficient chiral column with CP-Chirasil-Dex CB stationary phase was involved in headspace solid-phase microextraction-gas chromatography-mass spectrometry analysis of strawberry flavour in 6 strawberry cultivars, 7 samples of strawberry flavourings and 14 samples of strawberry syrups to evaluate the authenticity of flavour naturalness and reveal adulteration. Enantiomeric ratios of 8 selected chiral volatiles (methyl 2-methylbutanoate, ethyl 2-methylbutanoate, 2-methylbutanoic acid, linalool, α-ionone, γ-decalactone, γ-undecalactone, δ-dodecalactone) were evaluated. Seven chiral volatiles contributed to the revelation of synthetic origin. γ-Decalactone (enantiomeric ratios: 100∕0, 100∕0, 99∕1, 99∕1, 100∕0, and 99∕1 in strawberries; 100∕0 in 3 natural flavourings; 100∕0 in syrup with natural flavour) was the most contributive indicator of synthetic and natural strawberry flavour, followed by ethyl 2-methylbutanoate (enantiomeric ratios: 0∕100, 5∕95, 5∕95 in 3 natural flavourings, 0∕100 in syrup with natural flavour). The best chiral resolution was observed for α-ionone (R S >4). One syrup supposed to contain only natural strawberry flavouring was suspected to be adulterated regarding nearly racemic ratios of its four crucial chiral volatiles. Investigation of enantiomeric ratios of the unique selection of chiral volatiles and strawberry samples using the CP-Chirasil-Dex CB chiral column wider revealed possibilities for reliable recognition of strawberry flavour naturalness in complex matrices and in food samples in general.